2011
DOI: 10.1002/cncr.26713
|View full text |Cite
|
Sign up to set email alerts
|

How does health literacy affect quality of life among men with newly diagnosed clinically localized prostate cancer?

Abstract: BACKGROUND: Health literacy deficits affect half of the US overall patient population, especially the elderly, and are linked to poor health outcomes among noncancer patients. Yet little is known about how health literacy affects cancer populations. The authors examined the relation between health‐related quality of life (HRQOL) and health literacy among men with prostate cancer. METHODS: Data analysis included 1581 men with newly diagnosed clinically localized prostate cancer from a population‐based study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 27 publications
10
89
1
1
Order By: Relevance
“…age, income and education), social networks, comorbidities, and physical and psychological symptoms (Jansen, Koch, Brenner, & Arndt, 2010; Sun, Borneman, Koczywas, et al, 2012; Gupta, Lis, Granick, et al, 2006; Peters & Sellick, 2006). Increasingly, health literacy and effective patient-provider communication are also recognized as influencing care across the cancer continuum (e.g., cancer screening; symptom management; communication about end of life care) and subsequently may be a determinant of HRQOL among cancer patients (Aziz, Miller, & Randall, 2012; Berkman et al, 2011; Davis, Williams, Marine, Parker, & Glass, 2002; Song, Mishel, Bensen, Chen, Knafl, Blackard, et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…age, income and education), social networks, comorbidities, and physical and psychological symptoms (Jansen, Koch, Brenner, & Arndt, 2010; Sun, Borneman, Koczywas, et al, 2012; Gupta, Lis, Granick, et al, 2006; Peters & Sellick, 2006). Increasingly, health literacy and effective patient-provider communication are also recognized as influencing care across the cancer continuum (e.g., cancer screening; symptom management; communication about end of life care) and subsequently may be a determinant of HRQOL among cancer patients (Aziz, Miller, & Randall, 2012; Berkman et al, 2011; Davis, Williams, Marine, Parker, & Glass, 2002; Song, Mishel, Bensen, Chen, Knafl, Blackard, et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the association between patient-level health literacy levels and HRQOL among cancer patients and the results have been mixed (Song, Mishel, Bensen, Chen, Knafl, Blackard, et al, 2012; Hahn, Garcia, Du, & Cella, 2010). One study found that literacy was not an independent risk factor for poorer HRQOL after controlling for measurement bias and other covariates (Hahn, Cella, Dobrez, Weiss, Du, Lai et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Health-related quality of life is independently predicted by the level of one's health literacy [49,55,57]. Moreover, lower health literacy correlates with higher rates of complication [48], hospitalization [6,7,48], increased costs [27,53,62], and overall worse health [8,11,29,48,50,61].…”
Section: Introductionmentioning
confidence: 99%
“…This result demonstrates that individuals with better socialization with their peers and less difficulties in academic life have better functional health literacy. Another study (26) , which used the summaries of the physical and mental domains of the instrument SF12/version 2.0, also indicated a positive association between quality of life and the level of functional health literacy in men diagnosed with primary prostate cancer, in both domains. The existing literature only addresses the topic of quality of life and functional health literacy under chronic conditions like asthma (27) and heart disease (28) , or in specific areas such as oral health (29) .…”
Section: Discussionmentioning
confidence: 95%